Franz Kafka e os caluniados pela indústria cultural - Serrano, André Luís de Macedo (2018)
In the beginning of Franz Kakfa"s novel The Trial, someone slanders and holds Josef K. even though he did not do any harm. In this situation, K. looks for exits within his process, unable to identify who this slanderer would be. Along the way, he establishes contact with other characters who are equally accused by an inaccessible court. The slander that strikes the protagonist shows itself as an indictment against the collectivity. Court employees, who appear in everyday social spaces – from work to residence – act everywhere against K. and the accused. Taking these into account, we intend to analyze the dialogues between the accused and Josef K., unraveling the mechanisms of the kafkian court"s impersonal slander. Kafka"s writings, which date back to the first decades of the twentieth century, maintains its relevance by perceiving cultural elements that remain in contemporary capitalist society. Josef K."s absurd process has in itself a historic opening to think of the slandered contemporaries, both in criminal law and in the social realm of mass domination. The schematism of a slander machine – which could be identified as a phenomenon analogous to that of culture industry – reveals the violence that pervades the institutions of the rule of law, and which could be criticized as a support of the fiction of legal equality in bourgeois society. In class struggle, the court decides above the law, which appears as an empty, insubstantial form, without content, using the same law to decide the fate of oppressed collectivities, slandering K. and the accused of yesterday and today.